Designing a Health Consumer-Friendly Radiology Report Using a Patient-Centered Approach - (:unkn) unknown (My University, 2020)
In this dissertation, we needed to do four studies to reach the main objective of this dissertation. The fifth goal, which is the main one, is to reach a patient-friendly radiology report that can be easily understood. Study one: Full Radiology Report through Patient Web Portal: A Literature ReviewAlarifi, M., Patrick, T., Jabour, A., Wu, M., & Luo, J. (2020). Full Radiology Report through Patient Web Portal: A Literature Review. International Journal of Environmental Research and Public Health, 17(10), 3673. The aim of this study discusses the gap between the patient web portal and providing a full radiology report. A literature review was conducted to examine radiologists, physicians, and patients’ opinions and preferences of providing patients with online access radiology reports. The databases searched were Pubmed and Google Scholar and the initial search included 927 studies. After review, 47 studies were included in the study. We identified several themes, including patients’ understanding of radiology reports and radiological images, as well as the need for decreasing the turnaround time for reports availability. The existing radiology reports written for physicians are not suited for patients. Further studies are needed to guide and inform the design of patient friendly radiology reports. One of the ways that can be used to fill the gap between patients and radiology reports is using social media sites. Study two: Understanding patient needs and gaps in radiology reports through online discussion forum analysisAlarifi, M., Patrick, T., Jabour, A., Wu, M., & Luo, J. (2020). Understanding patient needs and gaps in radiology reports through online discussion forum analysis. Insights into imaging. Our objective is to investigate patient needs and understand information gaps in radiology reports using patient questions that were posted on online discussion forums. We leveraged online question and answer platforms to collect questions posted by patients to understand current gaps and patient needs. We retrieved six hundred fifty-nine (659) questions using the following sites: Yahoo Answers, Reddit.com, Quora, and Wiki Answers. The questions retrieved were analyzed and the major themes and topics were identified. The questions retrieved were classified into eight major themes. The themes were related to the following topics: radiology report, safety, price, preparation, procedure, meaning, medical staff, and patient portal. Among the 659 questions, 35.50% were concerned with the radiology report. The most common question topics in the radiology report focused on patient understanding of the radiology report (62 of 234 [26.49%]), image visualization (53 of 234 [22.64%]), and report representation (46 of 234 [19.65%]). We also found that most patients were concerned about understanding the MRI report (32%; n=143) compared with the other imaging modalities (n=434). Using online discussion forums, we discussed major unmet patient needs and information gaps in radiology reports. These issues could be improved to enhance radiology design in the future. Study three: The Development of Radiology Report Literacy Assessment Tool Diagnostic imaging and radiotherapy have become an important part of medical care. Patient understanding of radiology reports can improve their level of engagement and communication. There is little known about measuring a patient’s literacy level of a radiology report. The aim of this study is to design a tool to measure the radiology literacy of patients. We have designed and tested a radiology literacy tool. Participants were split into two groups and each group was given a radiology report sample to assess their understanding of the report. Participants also answered the radiology report literacy questions and the correlation between the understanding of the radiology report and radiology report literacy questions was calculated. The correlation between the report understanding and the radiology report literacy questions for the intervention and control groups was 0.537, P .00, and 0.517, P .00, respectively. Our radiology literacy tool had a good ability to measure the awareness of radiology (area under the receiver operator curve (95% CI: 0.72 (0.62-0.82)). We successfully designed a tool that can measure the radiology literacy of patients. This tool is considered one of the first tools that measures the level of patient knowledge in the radiology field. Study four: Health consumer social economic factors and health conditions as predictor for health literacy in radiology domain Patient literacy of radiology is imperative for patient engagement in care and management of their own health. Little is known about the factors that could predict patient literacy of radiology reports, testing, or treatment. This study aims to identify the most important factors of health consumer social economic and health conditions as a predictor of health literacy in the radiology domain. The study recruited 616 participants using Amazon.com’s Mechanical Turk (MTURK) and presented these participants with our questionnaire. We measured the level of participants’ radiology awareness, social factors, and health status. Descriptive statics including Chi-Square and multiple linear regression models were used to test if the factors could predict radiology literacy. The area under the receiver-operator curve was calculated to determine the prediction accuracy of the regression models. Multiple linear regression indicated that 15 of the 19 social-economic factors and health conditions were significantly associated with radiology literacy (P Study five: Designing a consumer-friendly radiology report using a patient-centered approach Patient portals have helped accelerate patient engagement in treatment. Patient understanding of radiology reports has become a necessity and we are working to design a patient-friendly radiology report that can be easily understood. We have based the design of this new radiology report on the results of a previous study that examined patient desires and needs by exploring their questions posted on online discussion forums. The current design was tested by presenting it in two groups, a control group, and an intervention group. In our evaluation, we relied on the following five concepts: understanding (quiz), cosmetics appearance, perceived ease of use, acceptance, and preference. The results showed that the new design outperformed the current design in all five concepts with an overall of (P
Keywords: Health Informatics; Radiology image; Radiology report